New records of the critically endangered Squatina squatina (Linnaeus, 1758) from Corsica, France - Lapinski, Matthieu (Array, 2019)
Angel Sharks are among the most threatened families of fish in the world. In the Mediterranean three species are present facing a severe depletion with several local extinction events as a result of over exploitation by fisheries. Hereby, we present 7 additional records of Squatina squatina from Corsica contributing to the new regional action plan for Angel Sharks in the Mediterranean Sea. Most records include juvenile specimens, indicating that the area might be a nursery ground for the species.